2016
DOI: 10.1111/jvim.14373
|View full text |Cite
|
Sign up to set email alerts
|

Serum N‐Terminal Type III Procollagen Propeptide: An Indicator of Growth Hormone Excess and Response to Treatment in Feline Hypersomatotropism

Abstract: BackgroundN‐terminal type III procollagen propeptide (PIIINP) is a biomarker of soft tissue proliferation. Hypersomatotropism (HS) is associated with soft tissue proliferation.HypothesisSerum PIIINP is increased in cats with HS and decreases with effective treatment, and may be an additional tool in the diagnosis and treatment of feline HS.AnimalsCats with uncomplicated diabetes mellitus (DM; n = 30) and with HS‐induced DM (HSDM; n = 30). Pre‐ and posttreatment samples were available from 5 cats undergoing rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Interstitial fibrosis is considered a characteristic histopathological finding in HCM in both humans and cats [ 1 ], and has also been described in both human [ 25 ] and feline [ 28 ] patients with acromegaly. Increased collagen turnover has also been demonstrated both in the cat [ 69 ] and human [ 70 ] with acromegaly. One previous study in humans found that myocardial fibrosis increases with age [ 71 ], so the presence of fibrosis in itself may not always indicate disease.…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial fibrosis is considered a characteristic histopathological finding in HCM in both humans and cats [ 1 ], and has also been described in both human [ 25 ] and feline [ 28 ] patients with acromegaly. Increased collagen turnover has also been demonstrated both in the cat [ 69 ] and human [ 70 ] with acromegaly. One previous study in humans found that myocardial fibrosis increases with age [ 71 ], so the presence of fibrosis in itself may not always indicate disease.…”
Section: Discussionmentioning
confidence: 99%
“…There was a consistent and marked reduction in serum IGF‐1 concentration after hypophysectomy in the current study. Normalization of serum IGF‐1 concentration to <300 ng/mL within 4 weeks of surgery occurred in 44 of 55 cats (80.0%), in contrast to variable serum GH and IGF‐1 concentration reductions after radiation therapy 8,16,18 . Normalization of IGF‐1 is an important biomarker for identifying those who have achieved normalization of endogenous GH.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Stereotactic radiation therapy for the treatment of 53 cats with HST and DM achieved reduced insulin requirements in 39 (95%) and diabetic remission in 13 (32%) of 41 cats. 9 Even if glycemic control improves, serum IGF-1 does not reduce significantly with hypofractionated radiotherapy regardless of changes in glycemic control, 8,16 resulting in progressive acromegalic features. 17 The single study to date on the use of stereotactic radiation therapy on cats with HST and DM did not report serum IGF-1 concentrations after treatment.…”
Section: Introductionmentioning
confidence: 99%